STRUCTURAL LEVEL OF ORGANIZATIONAL COMPETENCE DEVELOPMENT IN FUTURE PHYSICAL EDUCATION TEACHERS - Otabek Norboyevich Odilov (European Science Publishing, 2024)
Organizational skills are one of the qualities necessary for a modern teacher. This article discusses the theoretical aspects of the formation of organizational skills in physical education teachers.
Keywords: organizational skills, modern teacher, methodological guidelines, moral qualities, endurance, exactingness.